(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
The main objective of the article is to address the censorship of books during the cataloging process and the dissemination of books in society, analyzing its mechanics and challenges. Highlighting historical and contemporary cases, it reveals how censorship shapes the perception of reality and limits the diversity of perspectives. The research methodology is characterized by the theoretical bibliographical type, with a qualitative approach. The reflection ends up revealing recurring patterns of censorship in different contexts, influencing the formation of public opinion. Therefore, it tends to motivate readers to reflect on censorship in contemporary society, the role of the professional librarian during technical treatment, and considers measures to protect the expression and dissemination of information.